1991
DOI: 10.1210/endo-128-3-1285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Relaxin on Mammary Development in Ovariectomized Pregnant Gilts*

Abstract: The role of relaxin in mammary development was studied between days 80-110 of pregnancy in ovariectomized gilts given progesterone to maintain pregnancy. To obtain an objective measurement of lobulo-alveolar (parenchymal) composition, mammary glands were cut in cross-section through the teat, and the area of parenchymal tissue on the exposed face of the gland was determined. Ovariectomy on day 80 or 100 followed by progesterone replacement therapy resulted in a dramatic reduction in the rate of growth of mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 22 publications
1
43
0
1
Order By: Relevance
“…Although not classically considered to be involved in mammary development, research has shown that it is critical for normal mammary development in rodents (Bani et al, 1986), ruminants (Cowie et al, 1965), and pigs (Hurley et al, 1991;Bagnell et al, 1993). Relaxin is also thought to be involved in the inhibition of lactation prior to parturition (Harness & Anderson, 1975).…”
Section: Relaxinmentioning
confidence: 99%
“…Although not classically considered to be involved in mammary development, research has shown that it is critical for normal mammary development in rodents (Bani et al, 1986), ruminants (Cowie et al, 1965), and pigs (Hurley et al, 1991;Bagnell et al, 1993). Relaxin is also thought to be involved in the inhibition of lactation prior to parturition (Harness & Anderson, 1975).…”
Section: Relaxinmentioning
confidence: 99%
“…Relaxin is secreted by the CL, and levels are elevated in the peripheral blood during the last third of the approximately 114-day gestation period [12,13]. Relaxin may contribute to the maintenance of fetal viability as well as to the development of both the cervix [14,15] and mammary glands [16] during this period. Although blood levels of relaxin are relatively low during the first 2 mo of gestation [13], they may contribute to the initiation of uterine growth during early pregnancy [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of ovariectomized primiparous pigs demonstrated that endogenous relaxin not only is required for softening of the cervix, but also promotes development of the mammary gland parenchyma [23,44]. In contrast, it appears in rats that the major effects of relaxin on mammary growth and development target the nipple.…”
Section: Lactationmentioning
confidence: 99%